In vivo GSH depletion induces c-myc expression by modulation of chromatin protein complexes - Torres, Luis; Sandoval, Juan; Penella, Estela; Zaragozá, Rosa; García, Concha; Rodríguez, José Luis; Viña, Juan R.; García-Trevijano, Elena R. (Free radical biology & medicine, 2009)
We hypothesize that glutathione (GSH) fluctuations could have a prominent role in the modulation of c-myc expression through a mechanism affecting chromatin remodeling complexes. This could lead to an open chromatin structure accessible to transcription factors. We studied the in vivo effect of GSH depletion on these complexes bound to the c-myc promoter in the liver of l-buthionine-( S,R)-sulfoximine (BSO)-treated rats. Using chromatin immunoprecipitation we found that 3 h after BSO treatment the repressing complexes Id2 and Sin3A (part of a histone–deacetylase complex) were released from the c-myc promoter. STAT3 was phosphorylated and associated with its coactivator p300 with intrinsic acetyltransferase activity. Consequently, STAT3 was acetylated and bound to the c-myc promoter and histone H3 became hyperacetylated. At the same time, the RNApol II paused on the c-myc promoter was released, and the gene was overexpressed. After 6 h of BSO treatment, Id2/Sin3A returned to the c-myc promoter and the gene expression was down-regulated. Moreover, we observed a second peak of c-myc expression 48 h after BSO treatment, although at this time histone H3 was hypoacetylated and RNApol II paused, suggesting that this second peak was not subject to transcriptional control, but to posttranscriptional modulation. On the whole, our experiments suggest a novel mechanism for the effect of GSH on gene expression involving chromatin changes from a repressive to an open structure accessible to transcription factors such as STAT3.